Hybrid repair of cracked plates strengthened with composite patches and piezoelectric actuators - Aabid, Abdul (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
Active repair of a damaged structure using piezoelectric (PZT) actuators in controlling crack by electro-mechanical effect has played a significant role in recent years. Similarly, passive repair of damaged structures by means of various composite material patches have been widely studied by many researchers during the last four decades. This thesis proposes a hybrid repair of edge-cracked and center-cracked plates by using PZT actuators at the front of the plate, and a composite patch at the back of the plate via analytical, numerical, and experimental investigation. The models relate the Mode-I stress intensity factor (SIF), composite patch, and PZT actuator parameters for an edge-cracked and center-cracked aluminium plates, respectively. The electromechanical models are based on Linear Elastic Fracture Mechanics (LEFM), the singular stress at the crack tip, and the coupling effects of the PZT actuators. The first part of this thesis presents the finite element (FE) modelling and analysis of the present model and its validation with the existing results. In the second part, two types of analytical models were presented. In the first method, the solution was obtained from Rose's equations for the cracked plate integrated with a composite patch and passive PZT actuators under uniform uniaxial load. Then, the SIF for a cracked plate due to stress produced by PZT actuators was analytically modeled using the weighted functions method. The superposition principle method (SPM) was then used to superimpose the aforementioned solutions to yield the PZT actuators and composite patch hybrid SIF. In the second method, the analytical approach was driven from the parallel mean function (PMF), which is the combination of two separate solutions of passive and active analytical methods. Both proposed analytical models' results were verified against the finite element ones. The results demonstrated relatively low errors of less than 10% between the analytical and the FE values in all the cases studied in this work. Thus, the solutions obtained using the analytical approach are acceptable for the computation of SIF with reasonable accuracy. In the third part, an experimental investigation was carried out to verify the analytical and the FE results under Mode-I loading condition of an edge-cracked plate. Additionally, a parametric analysis was conducted to understand the influence of composite patch and PZT actuators on the mitigation of the SIF. In the fourth part of this thesis, the design of experiments (DOE) method was used to optimize the process parameters that lead to minimal SIF. Therefore, three parameters were used to optimize the reduction of SIF for the case of active and passive repair, whereas four parameters were used to investigate the optimal result of the hybrid repair. The present results demonstrated that the maximum reduction of SIF is accomplished by the application of the thick composite patch with thin adhesive bond coupled with thin actuators at higher voltage. In summary, this thesis investigated the possibility and pragmatism of the hybrid repair of edge-cracked and center-cracked plates under Mode-I loading condition with analytical, FE, experimental and optimization studies.